الضبط الإحصائی لجودة الکتل الخرسانیة - nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2010)
This paper presents a detailed explanation about the types of control charts or statistical adjustment, their importance, the qualities of their usage and the method of how to work with them. Besides, it presents the types, characteristics, and usage of the concrete blocks as a theoretical side of the paper. As an applied side of the paper, it introduces the method of using the control charts in determining the suitable decisions about the production process of manufacturing concrete blocks, and how it would help to show the actual variation in the produced units. Identification of defected units in an early stage of production will save materials and production costs.